Quantitative tracking of protein trafficking to the nucleus using cytosolic protein delivery by nanoparticle-stabilized nanocapsules - Ray, Moumita (Bioconjug Chem, 2015)
We describe a method for quantitative monitoring of subcellular protein trafficking using nanoparticle-stabilized nanocapsules for protein delivery. This method provides rapid delivery of the protein into the cytosol, eliminating complications from protein homeostasis processes found with cellularly-expressed proteins. After delivery, nuclear protein trafficking was followed by real time microscopic imaging. Quantitative analyses of the accumulation percentage and the import dynamics of the nuclear protein trafficking, demonstrate the utility of this method for studying intracellular trafficking systems.